The Effectiveness of Task-Based Language Teaching in Improving High School Students' English Listening and Speaking Skills: A Mixed Method Study - Riki Ruswandi; Paulina Novarita; Agim Mauludin; Genta Albani Mukti; Naila Eldisya Zainnasywa; Khansa Huzafa (Didaktika: Jurnal Kependidikan, 2025)
This study investigates the effectiveness of Task-Based Language Teaching (TBLT) in enhancing the listening and speaking skills of senior high school students in Indonesia. In this context, the development of communicative competence continues to face ongoing challenges. To comprehensively evaluate the impact of TBLT, the study employed a sequential mixed-methods explanatory design. The quantitative phase employed a quasi-experimental pre-test/post-test design with 77 students from three private schools, while the qualitative phase utilized interviews to deepen the Understanding. Quantitative results indicated that TBLT significantly improved listening (W = 461.5, p < .001) and speaking (W = 11.0, p < .001). However, the impact on speaking was statistically much stronger and consistent across school contexts. Thematic qualitative findings revealed that TBLT's effectiveness was strongly mediated by its ability to create a positive affective-motivational core; students and teachers reported increased enjoyment, confidence, and engagement as key factors for pedagogical success. It is concluded that TBLT is a highly effective approach, especially for productive skills. However, its success is context-dependent and strongly mediated by its ability to construct a psychologically supportive learning environment, underscoring the importance of careful pedagogical scaffolding.